Virulence and transcriptome profile of multidrug-resistant Escherichia coli from chicken - Hafiz I. Hussain (Nature Portfolio, 2017)
Abstract Numerous studies have examined the prevalence of pathogenic Escherichia coli in poultry and poultry products; however, limited data are available regarding their resistance- and virulence-associated gene expression profiles. This study was designed to examine the resistance and virulence of poultry E. coli strains in vitro and in vivo via antibiotic susceptibility, biofilm formation and adhesion, and invasion and intracellular survivability assays in Caco-2 and Raw 264.7 cell lines as well as the determination of the median lethal dose in two-day old chickens. A clinical pathogenic multidrug-resistant isolate, E. coli 381, isolated from broilers, was found to be highly virulent in cell culture and 1000-fold more virulent in a chicken model than other strains; accordingly, the isolate was subsequently selected for transcriptome analysis. The comparative gene expression profile of MDR E. coli 381 and the reference human strain E. coli ATCC 25922 was completed with Illumina HiSeq. 2500 transcriptome analysis. Differential gene expression analysis indicates that there are multiple pathways involved in the resistance and virulence of this highly virulent strain. The results garnered from this study provide critical information about the highly virulent MDR E. coli strain of poultry origin and warrant further investigation due to its significant threat to public health.